Genetic determinants of Helicobacter pylori vacuolating cytotoxin activity - Letley, Darren Peter (2011)
Helicobacter pylori infection is the main cause of peptic ulcer disease, and a significant risk factor for gastric adenocarcinoma, and mucosa-associated lymphoid tissue (MALT) lymphoma. A major virulence determinant is the vacuolating cytotoxin VacA, which causes cytoplasmic vacuolation, and other effects on epithelial cells. Sequence polymorphisms occur throughout vacA, the two most diverse regions being the signal region (s1 or s2) and the mid region (m1 or m2). Type s1/m1 strains are associated with toxigenicity in vitro, and greater disease risk. The published papers presented here aimed to investigate the role of vacA polymorphism on cytotoxin activity. By constructing isogenic hybrid variants of toxigenic and nontoxigenic strains, it was shown that differences within the signal region determined the vacuolating activity of the toxin, while differences in the mid-region conferred the cell-specificity of the vacuolating phenotype. These studies also led to the discovery of a new polymorphic determinant of vacuolating activity, the intermediate region, and it was shown that this region affected toxin activity in vitro, and was a better marker of gastric adenocarcinoma in an Iranian population than signal or mid-region type. Geographical variation in vacA allelic type exists, and it was shown that s1b-type strains, associated with reduced disease risk in the west, predominated in South Africa, which may have implications for the level of gastric disease in this region. The first occurrence of the rare s2/m1 vacA allele was also reported, supporting the view that vacA allelic diversity is due to recombination. Finally, VacA is an autotransporter, and possesses a single pair of cysteine residues near the C-terminus of the mature protein, spaced 11 residues apart. This feature is conserved among several autotransporters, and it is shown that these cysteines are required for high level VacA production, which may have implications for the autotransport process.